BEYOND THE CONTROVERSY: SOIL MICROBIOME DYNAMICS IN OIL PALM VS. NATURAL PEAT ECOSYSTEMS - Widiastuti, Happy; Pulunggono, Heru; Siswanto, Siswanto; Mubarak, Husni; Anwar, Syaiful; Taniwiryono, Darmono; Sumawinata, Basuki; Sabiham, Supiandi; Permatasari, Galuh (BRIN Publishing (Penerbit BRIN), 2025)
The increasing global demand for palm oil has driven the expansion of oil palm cultivation into peatland areas, raising concerns over environmental sustainability. This study investigates the impact of different land uses on soil microbial diversity and physicochemical properties by comparing three ecosystems: peat soil planted with oil palm (GS), peat soil with natural fern vegetation (GNS), and mineral soil cultivated with oil palm (MS). Physicochemical parameters including organic carbon, cellulose, and lignin content were analyzed, followed by 16S rRNA gene sequencing (V3-V4 regions) using the Illumina MiSeq platform. Sequencing data were processed using the QIIME2 pipeline and classified with the SILVA v.138 database. Results show that while MS had the highest microbial diversity, GS and GNS also supported diverse bacterial communities. Organic carbon, cellulose, and lignin were more abundant in GNS and GS than in MS, reflecting the influence of vegetation on soil composition. Dominant bacterial phyla across all sites included Proteobacteria, Actinobacteria, Firmicutes, and Acidobacteria. These findings suggest that oil palm cultivation on peatlands, when properly managed, does not necessarily reduce microbial diversity. Environmental factors such as vegetation cover, soil type, and water table levels play key roles in shaping microbial communities in tropical soils.